Hydrocarbon production catalyst, method of producing hydrocarbon production catalyst, and method of producing hydrocarbon
A highly active hydrocarbon production catalyst composed of iron, zinc, and sodium with controlled pore diameter is developed to enhance carbon dioxide conversion and hydrocarbon productivity, addressing the inefficiencies of existing catalysts in producing a range of hydrocarbon products.
Patent Information
- Application Number
- JP2023170610
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing hydrocarbon production catalysts from carbon dioxide and hydrogen have low one-pass conversion rates due to the stability of carbon dioxide, and they are not efficient in producing both light hydrocarbons with 3 to 4 carbon atoms and liquid hydrocarbons with 5 or more carbon atoms.
A hydrocarbon production catalyst composed mainly of iron, with zinc and sodium as cocatalysts, and having an average pore diameter of 25-50 nm, which is produced using a homogeneous precipitation method followed by impregnation of sodium, enhancing gas diffusion and promoting chain growth of hydrocarbons.
The catalyst achieves high carbon dioxide conversion and productivity of hydrocarbons with 3 to 4 carbon atoms, while also enabling high productivity of liquid hydrocarbons with 5 or more carbon atoms, thus improving the overall efficiency of hydrocarbon production.
Smart Images

Figure 2025060092000001 
Figure 2025060092000002 
Figure 2025060092000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a catalyst for producing hydrocarbons, a method for producing a catalyst for producing hydrocarbons, and a method for producing hydrocarbons. [Background technology]
[0002] In recent years, as environmental issues such as global warming have become more apparent, the importance of natural gas, which has a high H / C ratio compared to other hydrocarbon fuels and coal, can reduce carbon dioxide emissions, a substance that causes global warming, and is abundant in reserves, has been reevaluated, and demand for it is expected to continue to increase in the future. Under these circumstances, many places are actively working to convert natural gas into synthetic gas and then use the synthetic gas to produce hydrocarbons using the Fischer-Tropsch (FT) synthesis reaction.
[0003] For example, Patent Document 1 discloses a "hydrocarbon production catalyst comprising a compound having, as metal components, iron, sodium, and at least one member selected from the group consisting of zinc, manganese, and copper."
[0004] Patent Document 2 also discloses that "a catalyst for obtaining high-carbon α-olefins by carbon dioxide hydrogenation is characterized in that the catalyst contains Fe, and is a composite metal oxide catalyst of an alkali metal and another metal, in which the molar ratio of Fe to the metal is 1:1 to 1:0.05, so that the mass fraction in the alkali metal catalyst is 0.01% to 15%, the alkali metal includes one or more of Na, K, and Rb, and the other metal includes one or more of Mn, Zn, Cu, and Co." [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-3681 [Patent Document 2] China Patent Application Publication No. 109675573 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] However, the production of hydrocarbons from carbon dioxide and hydrogen, including those described in Patent Documents 1 and 2, has a problem in that the one-pass conversion rate is low due to the stability of carbon dioxide. In particular, while catalysts are generally used for the production of hydrocarbons, there is room for improvement in catalysts that can efficiently produce both the hydrocarbons with 3 to 4 carbon atoms used as LPG as well as liquid hydrocarbons with 5 or more carbon atoms used as kerosene.
[0007] It goes without saying that, in general, the higher the activity of the catalyst, the better. This is because the productivity per unit weight of catalyst increases, making it possible to reduce the size of the reactor and reduce equipment costs. Also, because less catalyst is required, it is possible to reduce catalyst costs. Therefore, high catalyst activity is a very important factor.
[0008] Therefore, an object of the present invention is to provide a highly active hydrocarbon production catalyst which has a high carbon dioxide conversion rate and which can ensure high productivity of hydrocarbons having 3 to 4 carbon atoms while also increasing the productivity of liquid hydrocarbons having 5 or more carbon atoms in the production of hydrocarbons using carbon dioxide and hydrogen as raw materials; a method for producing the hydrocarbon production catalyst; and a method for producing hydrocarbons using the hydrocarbon production catalyst. [Means for solving the problem]
[0009] The means for solving the problems include the following aspects. <1> It is mainly composed of iron, and also contains zinc and sodium. A hydrocarbon production catalyst having an average pore diameter of 25 to 50 nm. <2> The following formula (A Na )A NaThe value is 0.1 to 15.0 mass%. <1> The hydrocarbon production catalyst according to claim 1. Formula (A Na ):A Na =Na / Fe×100 Formula (A Na The symbol of each element in the formula indicates the mass of each element in the catalyst. <3> The average pore diameter is 35 to 50 nm. <1> or <2> The hydrocarbon production catalyst according to claim 1. <4> A first step of obtaining an oxide containing iron and zinc by homogeneous precipitation; a second step of supporting sodium on the surface of said oxide by impregnation; A method for producing a catalyst for producing hydrocarbons, comprising the steps of: <5> <1> ~ <3> A method for producing hydrocarbons using the hydrocarbon production catalyst according to any one of claims 1 to 4, A method for producing hydrocarbons, comprising contacting a mixed gas containing carbon dioxide and hydrogen with the hydrocarbon production catalyst to produce hydrocarbons. <6> Using a fixed bed, carbon dioxide and hydrogen are reacted in the presence of the catalyst to produce hydrocarbons. <5> A method for producing hydrocarbons according to claim 1. Effect of the Invention
[0010] According to the present invention, it is possible to provide a highly active hydrocarbon production catalyst which has a high carbon dioxide conversion rate and which ensures high productivity of hydrocarbons having 3 to 4 carbon atoms while also increasing the productivity of liquid hydrocarbons having 5 or more carbon atoms in the production of hydrocarbons using carbon dioxide and hydrogen as raw materials; a method for producing the hydrocarbon production catalyst; and a method for producing hydrocarbons using the hydrocarbon production catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described. In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits. In numerical ranges described in stages, the upper limit or lower limit value described in a certain numerical range may be replaced with the upper limit or lower limit value of another numerical range described in stages. In a numerical range, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples. When a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified. The term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved. A "combination of preferred aspects" is a more preferred aspect.
[0012] Additionally, "room temperature" refers to a temperature within the range of 23°C ± 3°C. The "hydrocarbon production catalyst" is also simply referred to as a "catalyst."
[0013] <Hydrocarbon production catalyst> The hydrocarbon production catalyst of the present invention contains iron as a main component, zinc and sodium, and has an average pore diameter of 25 to 50 nm.
[0014] The catalyst of the present invention, with the above-mentioned constitution, is a highly active catalyst that has a high carbon dioxide conversion rate in the production of hydrocarbons using carbon dioxide and hydrogen as raw materials, and that can increase the productivity of liquid hydrocarbons having a carbon number of 5 or more while ensuring the productivity of hydrocarbons having a carbon number of 3 to 4. The reason for this is presumed to be as follows. Increasing the average pore diameter of the catalyst enhances the gas diffusion of the reactant gases (carbon dioxide and hydrogen) and increases the carbon dioxide conversion. By adding zinc and sodium as promoters to a catalyst whose main component is iron, the chain growth of hydrocarbons is promoted and the yield of hydrocarbons with 3 to 4 carbon atoms is ensured, while the production of liquid hydrocarbons with 5 or more carbon atoms is increased, improving the yield of liquid hydrocarbons with 5 or more carbon atoms. In particular, when sodium coexists with zinc as a cocatalyst, the formation of iron carbide, which is the active species in the FT synthesis reaction, is promoted in an atmosphere of carbon dioxide and hydrogen, and methane (CH 4 ) and favors the production of long-chain hydrocarbons (i.e., hydrocarbons having 5 or more carbon atoms). Therefore, the catalyst of the present invention is presumed to be a highly active catalyst that has a high carbon dioxide conversion rate in the production of hydrocarbons using carbon dioxide and hydrogen as raw materials, and that can ensure high productivity of hydrocarbons having 3 to 4 carbon atoms while also increasing the productivity of liquid hydrocarbons having 5 or more carbon atoms.
[0015] The catalyst of the present invention will be described in detail below.
[0016] (Catalyst Components) The catalyst of the present invention contains iron as a main component and also contains zinc and sodium. Specifically, the catalyst of the present invention contains, for example, sodium supported on a catalyst support containing iron and zinc. However, the catalyst of the present invention may contain small amounts of impurities in addition to iron, zinc and sodium. Here, "a catalyst containing iron as a main component" means that the iron content is 60 mass% or more (preferably 80 mass% or more, 95 mass% or more, or 99 mass% or more) with respect to all components of the catalyst excluding oxygen. The mass of each component (iron, zinc, sodium, impurities) contained in the catalyst is measured by ICP-AES after subjecting the catalyst to pretreatment such as acid decomposition and alkali fusion.
[0017] In the catalyst of the present invention, Zn )A Zn The value (ie, the zinc content) is not particularly limited, but is preferably 0.1 to 40.0 mass %, more preferably 10.0 to 40.0 mass %. Formula (A Zn ):A Zn =Zn / (Fe+Zn)×100 Formula (A Zn The symbol of each element in the formula indicates the mass of each element in the catalyst.
[0018] Zinc in the catalyst is considered to be in the form of an oxide. Zn )A Zn Values (i.e. zinc content) are calculated as the sum of all chemical forms of zinc. Formula (A Zn )A Zn It is estimated that when the value (i.e., the zinc content) is 0.1 mass% or more, the basicity of the catalyst surface is improved, promoting the formation of iron carbide, which is presumed to be an active species of iron, and promoting the adsorption of carbon dioxide, which is the raw material gas, onto the catalyst surface. Formula (A Zn )A Zn When the value (i.e., the zinc content) is 40.0 mass % or less, the relative decrease in the content of iron, which is an active species, is suppressed. Therefore, the formula (A Zn )A Zn When the value (i.e., the zinc content) is within the above range, the catalyst is likely to be highly activated, and the carbon dioxide conversion rate, the productivity of hydrocarbons having 3 to 4 carbon atoms, and the productivity of liquid hydrocarbons having 5 or more carbon atoms are likely to be improved.
[0019] In the catalyst of the present invention, Na )A Na The value (that is, the sodium content) is not particularly limited, but is preferably 0.1 to 15.0 mass %, more preferably 2.0 to 10.0 mass %. Formula (A Na ):A Na =Na / Fe×100 Formula (A Na The symbol of each element in the formula indicates the mass of each element in the catalyst.
[0020] In the catalyst, iron is actually in the form of iron oxide and may contain impurities, but A in formula (ANa) Na The value (i.e., the sodium content) is calculated as a percentage of iron excluding impurities. Sodium is considered to be in the form of an oxide, but the formula (A Na )A Na Values (i.e. sodium content) are calculated based on the sum of all chemical forms of sodium. Formula (A Na )ANa When the value (i.e., the sodium content) is 0.1 mass% or more, it is estimated that, like zinc, the basicity of the catalyst surface is improved, promoting the formation of iron carbide, which is presumed to be an active species of iron, and promoting the adsorption of carbon dioxide, which is the raw material gas, onto the catalyst surface. Formula (A Na )A Na When the value (i.e., the sodium content) is 15.0 mass % or less, the relative decrease in the content of iron, which is an active species, is suppressed. Therefore, the formula (A Na )A Na When the value (i.e., the sodium content) is within the above range, the catalyst is likely to be highly activated, and the carbon dioxide conversion rate, the productivity of hydrocarbons having 3 to 4 carbon atoms, and the productivity of liquid hydrocarbons having 5 or more carbon atoms are likely to be improved.
[0021] In the catalyst of the present invention, iron, zinc and sodium exist mainly as oxides when the catalyst is calcined (unreduced) in the catalyst production method described below, but exist mainly as metals when the catalyst is reduced. Furthermore, metals and oxides are mixed and the ratio thereof changes depending on the production conditions, use conditions, storage conditions, etc.
[0022] In the catalyst of the present invention, even if iron, zinc and sodium exist as oxides, they are reduced and metallized during the reaction by the reducing atmosphere during the reaction, and perform the necessary catalytic function, so they do not have to exist only in the metallic state. Note that there may be cases where trace amounts of raw materials (precursors) remain in the catalyst.
[0023] (Catalyst properties) The average pore diameter of the catalyst of the present invention is 25 to 50 nm. The smaller the average pore size, the larger the specific surface area can be, but if the average pore size is 25 nm or more, gas diffusion in the pores is promoted, and hydrogen and carbon dioxide react efficiently. In addition, the diffusion rate of the generated hydrocarbons in the pores also increases, which contributes to an increase in the reaction rate. On the other hand, when comparing at a constant pore volume, the larger the average pore diameter, the smaller the specific surface area, and the lower the degree of dispersion of the active metal in the catalyst tends to be. Therefore, the pore diameter is set to 50 nm or less. Therefore, by setting the average pore diameter of the catalyst of the present invention within the above range, the catalyst is highly activated, and the carbon dioxide conversion rate, the productivity of hydrocarbons having 3 to 4 carbon atoms, and the productivity of liquid hydrocarbons having 5 or more carbon atoms are improved. The average pore diameter of the catalyst of the present invention is preferably from 35 to 50 nm, more preferably from 40 to 50 nm.
[0024] In order to set the average pore diameter of the catalyst of the present invention within the above range, the method for producing the catalyst includes a method for obtaining an oxide containing iron and zinc by a homogeneous precipitation method.
[0025] The specific surface area of the catalyst of the present invention is 20 to 200 m 2 / g is preferable, and 30 to 100m 2 / g is more preferred. The specific surface area of the catalyst is 20m 2 When the iron content is 1 / g or more, sufficient activity is easily exhibited in the reaction for producing hydrocarbons using carbon dioxide and hydrogen as raw materials. In addition, the dispersion degree of iron increases, improving the contribution efficiency to the reaction. The specific surface area of the catalyst is 200m 2 When the pore volume and average pore diameter are both within the intended range, it becomes easier to simultaneously achieve the intended range.
[0026] The pore volume of the catalyst of the present invention is preferably from 0.1 to 1.0 mL / g, more preferably from 0.2 to 0.8 mL / g. When the pore volume of the catalyst is 0.1 to 1.0 mL / g, it becomes easy to simultaneously satisfy the target ranges for the average pore diameter and specific surface area.
[0027] Here, the average pore diameter of the catalyst is measured by measuring the specific surface area (S) and the pore volume (V) of the catalyst, and the average pore diameter is calculated according to the formula: average pore diameter (nm) = 4 × 10 3 [Pore volume (cm 3 / g) / Specific surface area (m 2 The average pore diameter is calculated by the formula (1 / g). The specific surface area (S) of the catalyst is calculated by obtaining an adsorption isotherm by nitrogen adsorption method, and analyzing the obtained adsorption isotherm by BET (Brunauer-Emmett-Teller) method. The BET specific surface area is calculated by performing BET analysis in the range of relative pressure of the isotherm during nitrogen gas adsorption from 0.10 to 0.0.25. The pore volume (V) of a catalyst is the total volume of pores of all diameters and is calculated using the formula: total pore volume (cm 3 / g) = adsorbed amount × molecular weight of adsorbate / (22414 × density of adsorbate (g / cm 3 The amount of adsorption is calculated by linearly interpolating the adsorption data within the relative pressure range set above. As a pretreatment prior to carrying out the nitrogen adsorption method, the catalyst is subjected to a heat treatment in a vacuum at 150° C. for 2 hours in order to remove moisture from within the pores of the catalyst. The measurement temperature for the nitrogen adsorption method is 77K.
[0028] (Catalyst manufacturing method) The method for producing the catalyst of the present invention is, for example, A first step of obtaining an oxide containing iron and zinc by homogeneous precipitation; a second step of depositing sodium on the surface of the oxide by impregnation; has.
[0029] According to the method for producing a catalyst of the present invention, it is possible to obtain a highly active hydrocarbon production catalyst (i.e., the catalyst of the present invention having an average pore diameter in the above range) which has a high carbon dioxide conversion rate and which can increase the productivity of liquid hydrocarbons having 5 or more carbon atoms while ensuring high productivity of hydrocarbons having 3 to 4 carbon atoms.
[0030] -First step- In the first step, an oxide containing iron and zinc is obtained by homogeneous precipitation. Specifically, in the first step, an aqueous solution of an iron compound and a zinc compound as raw materials (precursors) mixed with urea as a precipitant is heated and aged to obtain a precipitate, which is then washed, dried, and calcined to obtain an oxide mainly composed of iron.
[0031] Here, the homogeneous precipitation method preferably uses urea as a precipitant. In the homogeneous precipitation method using urea as a precipitant, the average pore diameter can be easily controlled to the above range, and the catalyst of the present invention can be easily obtained.
[0032] In the homogeneous precipitation method, when the iron compound and zinc compound used as the raw material (precursor) are subjected to drying and reduction treatment, or drying, calcination and reduction treatment, counter ions (e.g., Fe(NO ) in the case of iron nitrate) are added to the precipitate after precipitation. 3 ) 2 In (NO 3 ) - There are no particular limitations on the compound, so long as it is a compound that volatilizes and dissolves in a solvent. Specifically, the iron compound and zinc compound may be used in the form of nitrate, carbonate, acetate, chloride, acetylacetonate, etc. The iron compound and zinc compound may be used in the form of hydrate of nitrate, carbonate, acetate, or chloride. From the viewpoint of reducing production costs and ensuring a safe production working environment, it is preferable to use, as the iron compound and the zinc compound, water-soluble compounds which can be used in an aqueous solution during the precipitation operation. In particular, it is preferable to use nitrates or acetates as the iron and zinc compounds, since these are easily converted to iron oxide during firing, and the subsequent reduction treatment of the iron oxide and zinc oxide is also easy.
[0033] -Second step- In the second step, sodium is supported on the surface of the oxide by impregnation. Specifically, in the second step, for example, the obtained oxide is impregnated with an aqueous solution of a sodium compound as a raw material (precursor), and then dried and fired in a vacuum atmosphere to support sodium on the surface of the oxide.
[0034] Here, the method for supporting sodium on the catalyst is not limited to the impregnation method, but may be any well-known treatment method such as the incipient wetness method, the precipitation method, or the ion exchange method. However, since it is preferable to support sodium on the surface of the catalyst (i.e., sodium is supported on the surface of the oxide), the impregnation method and the ion exchange method are preferable as the method for supporting sodium on the catalyst, and the impregnation method is more preferable. When the impregnation method is adopted as a method for supporting sodium on the surface of the oxide, it is preferable to irradiate the oxide with sodium supported on its surface with ultrasonic waves before drying or calcination after the supporting operation, since sodium can be supported uniformly on the oxide. In addition, drying under a vacuum atmosphere after the supporting operation is preferable, since sodium is dispersed into the oxide pores.
[0035] As for the sodium compound as the raw material (precursor), a counter ion (e.g., NaNO for sodium nitrate) is added when drying and / or calcining after the loading. 3 In (NO 3 ) - There are no particular limitations on the compound as long as it is a compound that volatilizes and dissolves in a solvent. Specifically, the sodium compound that can be used includes nitrates, carbonates, acetates, chlorides, acetylacetonates, and the like. From the viewpoint of reducing production costs and ensuring a safe production work environment, it is preferable to use a water-soluble compound that can be used in an aqueous solution during the supporting operation as sodium. In particular, when sodium nitrate or sodium acetate is used as sodium, it is preferable because it is easily converted into iron oxide during firing, and the subsequent reduction treatment of sodium oxide is also easy.
[0036] Through the above steps, the catalyst of the present invention is obtained. The catalyst of the present invention obtained through the above steps is a compound mainly composed of oxides, but may be subjected to a reduction treatment as a post-treatment. If the reduction conditions are made severe by increasing the temperature or time of the reduction treatment, the proportion of metal compounds in the catalyst that are reduced from the oxide state to the metallic state after the reduction treatment increases, and if the reduction treatment is extremely severe, it is possible to reduce the catalyst to a state of only active metals. However, under typical reduction conditions, the catalyst of the present invention often enters a chemical state that partially contains iron oxide, zinc oxide, and sodium oxide.
[0037] The catalyst after reduction treatment must be handled carefully so as not to be oxidized and deactivated by contact with the air. It is preferable to carry out a stabilization treatment so as to isolate the iron metal surface of the catalyst from the atmosphere, since this makes it possible to handle the catalyst in the atmosphere. Stabilization treatments include passivation, which involves exposing the catalyst to nitrogen, carbon dioxide, or an inert gas containing a low concentration of oxygen to oxidize only the very surface layer of the active metal on the catalyst surface, and immersing the catalyst in a reaction solvent or molten wax to isolate it from the atmosphere when the reaction to produce hydrocarbons from carbon dioxide and hydrogen as raw materials is carried out in a liquid phase. However, the stabilization treatment should be appropriate depending on the situation.
[0038] (Method of producing hydrocarbons) Next, a method for producing hydrocarbons by reacting carbon dioxide with hydrogen using the catalyst of the present invention will be described. In the method for producing hydrocarbons of the present invention, a mixed gas containing carbon dioxide and hydrogen is brought into contact with the above-mentioned hydrocarbon production catalyst to produce hydrocarbons.
[0039] The reaction conditions are not particularly limited, but good results are likely to be obtained when the reaction temperature is 280 to 400° C. and the reaction pressure is 1.5 to 6.0 MPa.
[0040] If the reaction temperature is below 280°C, sufficient catalytic activity may not be exhibited. If the reaction temperature exceeds 400°C, the selectivity for by-products such as methane increases and the catalyst life may decrease. Therefore, the reaction temperature is preferably set in the range of 280 to 400°C.
[0041] If the reaction pressure is lower than 1.5 MPa, sufficient catalytic activity may not be exhibited. If the reaction pressure exceeds 6.0 MPa, there is no problem in terms of catalyst activity, but the pressure resistance design of the plant will be set high, resulting in increased equipment costs. Therefore, the reaction pressure is preferably set in the range of 1.5 to 6.0 MPa.
[0042] The reaction format may be selected depending on the reaction conditions and is not particularly limited, such as a fixed bed or a slurry bed, but from the viewpoint of catalytic activity, a reaction temperature of more than 300° C. is preferable, and a fixed bed is suitable. In a slurry bed, it is preferable that a solvent that becomes liquid under the reaction conditions is produced by the reaction, but at reaction temperatures exceeding 300° C., most hydrocarbons are in a gaseous state, making it difficult to maintain the reaction in a slurry bed. For this reason, it is preferable to use a fixed bed as the reaction format and react carbon dioxide with hydrogen in the presence of a catalyst to produce hydrocarbons.
[0043] When a fixed bed is used, the catalyst is preferably molded into pellets, taking into consideration the pressure loss in the reactor.
[0044] In the case of a relatively small-scale plant in which a carbon dioxide conversion plant is installed at a source of carbon dioxide emission, a microchannel reactor may be advantageous. However, in consideration of filling a catalyst into a flow path of millimeter order or less, the particle size of the catalyst is preferably about 20 to 250 μm.
[0045] In the method for producing hydrocarbons of the present invention, the mixed gas of carbon dioxide and hydrogen as the reaction gas (i.e., the raw material gas) is preferably a gas in which the total of carbon dioxide and hydrogen is 50 volume % or more of the total, from the viewpoint of productivity, and in particular, the molar ratio of hydrogen to carbon dioxide (hydrogen / carbon dioxide) is preferably in the range of 0.5 to 4.0. This is because, when the molar ratio of hydrogen to carbon dioxide is 0.5 or more, the amount of hydrogen present in the raw material gas is sufficient, so that the hydrogenation reaction of carbon dioxide easily proceeds and productivity is high. On the other hand, when the molar ratio of hydrogen to carbon dioxide is 4.0 or less, the amount of carbon dioxide present in the raw material gas is sufficient, so that, together with the high activity of the catalyst according to the present invention, the productivity of hydrocarbons is high. EXAMPLES
[0046] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0047] (Examples 1 to 6, Comparative Example 5) The aqueous solution of the raw materials (precursors) iron nitrate hydrate and zinc nitrate hydrate mixed with urea as a precipitant is heated at 90°C for 4 hours to obtain a precipitate. The precipitate is washed, dried at 120°C for 12 hours, and calcined at 400°C for 4 hours to obtain the oxide. The obtained oxide was impregnated with an aqueous solution of sodium nitrate, ultrasonically treated, dried at 120°C for 12 hours in a vacuum atmosphere, and calcined at 400°C for 4 hours to obtain a catalyst. However, the amounts of iron nitrate hydrate, zinc nitrate hydrate, and sodium nitrate are determined based on the iron content of the resulting catalyst, the formula (A Na )A Na Value (Na content), formula (A Zn )A Zn The value (Zn content) was adjusted to the value shown in Table 1.
[0048] Comparative Example 1 The catalyst was synthesized in one step using a hydrothermal synthesis method as follows. An aqueous solution of iron nitrate, zinc nitrate, and sodium hydroxide was placed in a Teflon tube and heated in an autoclave at 180° C. for 8 hours. The resulting product was washed and the amount of sodium was adjusted to obtain a catalyst. However, the amounts of iron nitrate hydrate, zinc nitrate hydrate, and sodium nitrate are determined based on the iron content of the resulting catalyst, the formula (A Na )A Na Value (Na content), formula (A Zn )A Zn The value (Zn content) was adjusted to the value shown in Table 1.
[0049] (Comparative Examples 2 to 3) The catalyst was obtained by synthesizing iron oxide using a hydrothermal synthesis method, and then supporting zinc and sodium, or sodium, on the iron oxide by an impregnation method. A solution containing an iron source (iron nitrate) was treated in an autoclave, a reaction vessel capable of heating and pressurizing, to obtain iron oxide. Thereafter, the iron oxide was impregnated with zinc nitrate and sodium hydroxide, or a solution containing sodium hydroxide, and then dried at 120°C for 12 hours and calcined at 400°C for 4 hours to obtain a catalyst. Note that the amounts of iron nitrate hydrate, zinc nitrate hydrate, and sodium nitrate were determined based on the iron content of the obtained catalyst, the amount of the iron nitrate hydrate being determined based on the amount of the iron nitrate hydrate in the catalyst, the amount of the zinc nitrate hydrate in the catalyst, and the amount of the sodium nitrate in the catalyst. Na )A Na Value (Na content), formula (A Zn )A Zn The value (Zn content) was adjusted to the value shown in Table 1.
[0050] Comparative Example 4 The catalyst was obtained by synthesizing an oxide containing iron and zinc using a coprecipitation method, and then supporting sodium on the oxide using an impregnation method. The raw materials (precursors) iron nitrate hydrate and zinc nitrate hydrate were dissolved in an aqueous solution, and a sodium carbonate aqueous solution was added as a precipitant to precipitate a composite hydroxide of iron and zinc. The precipitated composite oxide was then aged at 80°C for 4 hours, dried at 120°C for 12 hours, and calcined at 400°C for 4 hours to obtain the composite oxide. Thereafter, the iron oxide was impregnated with zinc nitrate and sodium hydroxide, or a solution containing sodium hydroxide, and then dried at 120°C for 12 hours and calcined at 400°C for 4 hours to obtain a catalyst. However, the amounts of iron nitrate hydrate, zinc nitrate hydrate, and sodium nitrate are determined based on the iron content of the resulting catalyst, the formula (A Na )A Na Value (Na content), formula (A Zn )A Zn The value (Zn content) was adjusted to the value shown in Table 1.
[0051] (characteristic) [Average pore diameter of catalyst] The average pore diameter of each example catalyst was measured according to the method previously described.
[0052] [CO 2 Conversion rate, CO selectivity, selectivity of each hydrocarbon, yield of each hydrocarbon] The reactivity of the catalyst in each example was evaluated as follows. The catalyst of each example was packed into a tubular reactor. After the catalyst was packed into the reactor, a reduction treatment was performed, and the catalyst was reduced under the conditions of 290°C and 3.0 MPa, so that W (catalyst mass) / F (synthetic gas flow rate); (g h / mol) = 5.0, and F (reactant gas (H 2 / CO 2 The composition of the supply gas and the autoclave outlet gas was determined by gas chromatography, and the following reaction characteristics were calculated. CO 2 Conversion rate CO selectivity Selectivity of hydrocarbons with one carbon atom (methane) (C 1 (referred to as "selection rate") Selectivity of hydrocarbons with carbon number 2 (ethane) (C 2 (referred to as "selection rate") Selectivity of hydrocarbons with carbon numbers of 3 to 4 ("C 3-4 (referred to as "selection rate") Selectivity for hydrocarbons with carbon numbers of 5 or more ("C 5+ (referred to as "selection rate") - Yield of hydrocarbons with carbon numbers of 3 to 4 ("C 3-4 (referred to as "yield") - Yield of hydrocarbons with carbon number of 5 or more ("C 5+ (referred to as "yield")
[0053] In addition, CO 2 The conversion rate and each selectivity were calculated based on the following formulas.
number
[0054] Each yield was calculated based on the following formula.
number
[0055] [Table 1]
[0056] From the above results, it can be seen that the catalyst of this example is a highly active hydrocarbon production catalyst that has a higher carbon dioxide conversion rate than the catalyst of the comparative example, and that can ensure high productivity of hydrocarbons having 3 to 4 carbon atoms while also increasing the productivity of liquid hydrocarbons having 5 or more carbon atoms.
Claims
1. It is mainly composed of iron, and also contains zinc and sodium. A hydrocarbon production catalyst having an average pore diameter of 25 to 50 nm.
2. The following formula (A Na ) A Na 2. The hydrocarbon production catalyst of claim 1, wherein the value is from 0.1 to 15.0 wt. %. Formula (A Na ): A Na = Na / Fe × 100 Formula (A Na ) indicates the mass of each element in the catalyst.
3. 2. The hydrocarbon production catalyst according to claim 1, wherein the average pore diameter is from 35 to 50 nm.
4. A first step of obtaining an oxide containing iron and zinc by homogeneous precipitation; a second step of supporting sodium on the surface of said oxide by impregnation; A method for producing a catalyst for producing hydrocarbons, comprising the steps of:
5. A method for producing hydrocarbons using the hydrocarbon production catalyst according to any one of claims 1 to 3, comprising the steps of: A method for producing hydrocarbons, comprising contacting a mixed gas containing carbon dioxide and hydrogen with the hydrocarbon production catalyst to produce hydrocarbons.
6. Using a fixed bed, carbon dioxide and hydrogen are reacted in the presence of the catalyst to produce hydrocarbons. The method for producing hydrocarbons according to claim 5 .
Citation Information
Patent Citations
Catalyst for preparing high-carbon alpha-olefin by hydrogenation of carbon dioxide, and preparation method and application
CN109675573A
Catalyst for producing hydrocarbon, production method of catalyst for producing hydrocarbon, and production method of hydrocarbon
JP2021003681A